A simple water balance model adapted for soil water repellency: application on Portuguese burned and unburned eucalypt stands. Issue 3 (26th August 2015) - Nunes, João Pedro; Malvar, Maruxa; Benali, Akli Ait; Rial Rivas, María Ermitas; Keizer, Jan Jacob
Abstract: Soil water repellency can impact soil hydrology, overland flow generation and associated soil losses. However, current hydrological models do not take it into account, which creates a challenge in repellency‐prone regions. This work focused on the adaptation for soil water repellency of a daily water balance model. Repellency is estimated from soil moisture content using site‐specific empirical relations and used to limit maximum soil moisture. This model was developed and tested using approximately 2 years of data from one long‐unburned and two recently burned eucalypt plantations in northern Portugal, all of which showed strong seasonal soil water repellency cycles. Results indicated important improvements for the burned plantations, with the Nash–Sutcliffe efficiency increasing from −0.55 and −0.49 to 0.55 and 0.65. For the unburned site, model performance was already good without the modification and efficiency only improved slightly from 0.71 to 0.74, mostly due to the better simulation of delayed soil wetting after dry periods. Results suggested that even a simple approach to simulate soil water repellency can markedly improve the performance of hydrological models in eucalypt forests, especially after fire. Copyright © 2015 John Wiley & Sons, Ltd.